2019
DOI: 10.1002/admt.201900513
|View full text |Cite
|
Sign up to set email alerts
|

Design and Fabrication of a Multifunctional Flexible Absorber (Flexorb) in the UV–Vis–NIR Wavelength Range

Abstract: breaking strain. [18] 4) The creasing in thin foils during fabrication and operations pose another challenge. [19] 5) The rigid and metallic foil-based absorbers will be difficult to mount on surfaces with complex geometry and curved contours. 6) The integrity of these absorbers with variety of underlying surfaces made of metals and polymers have not been established yet. To overcome some of these issues, flexible optical absorbers are developed using nanocomposites or thin metal foils as base substrate. [9,20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The tensile strength could be further increased to 2.3 MPa with the introduction of microcavities on the surface, which could be ascribed mainly to the trap of PANI in the pillars. [ 43 ] To further explore the mechanical stability of the composite sheet, 500 cycles of loading–unloading fatigue test were performed under the stretch strain of 0–50%. The sample could be recovered in terms of the length and width dimensions after 500 cycles as shown in Figure a.…”
Section: Resultsmentioning
confidence: 99%
“…The tensile strength could be further increased to 2.3 MPa with the introduction of microcavities on the surface, which could be ascribed mainly to the trap of PANI in the pillars. [ 43 ] To further explore the mechanical stability of the composite sheet, 500 cycles of loading–unloading fatigue test were performed under the stretch strain of 0–50%. The sample could be recovered in terms of the length and width dimensions after 500 cycles as shown in Figure a.…”
Section: Resultsmentioning
confidence: 99%
“…26,27,35 PDMS nanocomposites reinforced by combining ZnO, Fe, and CNT nanoparticles have demonstrated a similar absorption value to the ones obtained from the GnF/PDMS studied in this work. 24 The absorption in the current study can be further verified by analyzing the reflectance spectra of the nanocomposite films. While pure PDMS transmitted around 92% of light, incorporation of GnF, even at 1 wt %, significantly diminishes the transmittance down to less than 0.2% in the entire spectrum, indicating that all GnF/PDMS nanocomposites studied in this work are opaque (Figure S6).…”
Section: Optical and Photothermal Studies Of Gnf/pdms Nanocomposite F...mentioning
confidence: 99%
“…20−24 Due to superior absorption capabilities and their photostability, carbon-based photothermal materials such as graphite, CNT, graphene flakes, and carbon nanoparticles have been used to fabricate PDMS nanocomposites for various solar-powered applications. [20][21][22]24,25 In particular, graphite is often the immediate choice because of its lost cost and ease of availability. 25−29 However, natural graphite has higher reflectance at the air−dielectric interface, limiting solar energy absorption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For safeguarding optical instruments present on the satellites and to suppress stray light, various types of black coatings are developed in past few years . Most of these black surfaces are fabricated using surface texturing, optical grating, etching, nano composite or by applying coating of different nanomaterials on the surface of interest. It is observed that the surface texturing/etching followed by nano‐coating shows enhanced light trapping capacity in a broader wavelength range.…”
Section: Introductionmentioning
confidence: 99%